Business News as a Source of Information Literacy in Marketing. Issue 2 (4th May 2017) - Fowler, Kendra; Bridges, Eileen
Abstract : Among the proficiencies that marketing students should acquire, information literacy, the ability to gather and apply pertinent information to aid in decision making, is commonly overlooked. In this article, information literacy is explored along four complementary dimensions: instrumental, conceptual, reflective, and symbolic. Furthermore, the importance of information literacy is discussed, and two author-tested class exercises (blogging and live case studies) are presented. The goal is to encourage marketing educators to include business news as an active part of course designs and, thereby, to enhance student knowledge of current business events as well as understanding of their implications in decision making.